2014
DOI: 10.3329/bjb.v42i2.18023
|View full text |Cite
|
Sign up to set email alerts
|

Limnology of lake Rainkhyongkain of Bangladesh with a new record of Marchantia polymorpha L. var. aquatica Nees

Abstract: In lake Rainkhyongkain, water temperature, pH, conductivity and total dissolved solids (TDS) were recorded 33.5°C, 7.39, 308 µS/cm and 49 mg/l, respectively. The mean values (n = 4) of dissolved oxygen content (DO), alkalinity, soluble reactive phosphorus (SRP), soluble reactive silicate (SRS) and NO 3 -N were 7.93 ± 0.78 mg/l, 1.70 ± 0.12 meq/l, 17.25 ± 0.62 µg/l, 10.44 ± 0.72 mg/l and 34.00 ± 4.00 µg/l, respectively. The phytoplankton biomass as chlorophyll a (chl a) was found very low (4.93 ± 0.51 µg/l) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…All samples were transported to the laboratory and processed within 24 hours of collection. Different autecological parameters were studied with the help of Alfasane et al (2013); Golterman et al (1978) and Huq and Alam (2005). Photographs of internal section of leaf and stem were taken with the help of a compound microscope, Nikon (Optiphot, UFX-11A) fitted with a camera (Nikon FX-35 WA, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…All samples were transported to the laboratory and processed within 24 hours of collection. Different autecological parameters were studied with the help of Alfasane et al (2013); Golterman et al (1978) and Huq and Alam (2005). Photographs of internal section of leaf and stem were taken with the help of a compound microscope, Nikon (Optiphot, UFX-11A) fitted with a camera (Nikon FX-35 WA, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…A large number of aquatic macrophytes have been found of these habitats. Alfasane et al (2010Alfasane et al ( , 2013Alfasane et al ( , 2019Alfasane et al ( , 2020Alfasane et al ( , 2021Alfasane et al ( , 2022Alfasane et al ( , 2023 have been reported 11 species of aquatic macrophytes either as new to science, new records and new occurrence including the present species from Bangladesh. Recently Alfasane et al (2023) reported Elodea canadensis Michx.…”
Section: Introductionmentioning
confidence: 99%
“…range of species and importance values (number, biomass, productivity) of individuals, determine the species diversity of a community (Odum, 1996). A number of limnological studies have been conducted on several freshwater bodies in Bangladesh but none of them encompasses the diversity of aquatic macrophyts in oxbow lakes (Khondker et al, 2012;Alfasane et al, 2013;Basak et al, 2015). So the present study was aimed to evaluate the diversity of aquatic macrophytes and water quality from a well-known oxbow lake called "Jhanpa Baor".…”
Section: Introductionmentioning
confidence: 99%